A Diasporic Character’s Struggle in Her Homeland in the Mango Season - Ilham Burhan Alam (Fakultas Ilmu Budaya, 2025)
This thesis explores the multifaceted identity conflicts of Priya Rao, the protagonist of Malladi's novel The Mango Season, who returns to her native India after living in the US for several of years. The study explores how diasporic experiences result in cultural hybridity, internal conflict, and alienation, especially when people face the traditional expectations of their home culture after being exposed to a Western way of life. Hall’s Cultural Identity is used as the main theoretical framework. The type of this research is qualitative, supported by close reading of the novel and interviews with the author. In order to maintain cultural unity, it examines how Priya's Americanized ideals of independence, love, and self-expression conflict with those of her traditional Indian family, which include planned marriage, submission, and silence. Priya's battle turns into a point of conflict between personal identity and societal norms. Identity Crisis, Patriarchy and Gender Expectations, Cultural Symbols and Silence, and Alienation and Resistance are the main themes. Priya's broken sense of self and her internal identity crisis are examined. While silence and cultural symbols represent resistance and connection, patriarchy limits female freedom. Alienation complicates Priya's sense of alienation, while her peaceful resistance to social norms is powerful. Amulya Malladi's feminist views on South Asian women and traditional Indian cultural frameworks are also examined in the thesis. The Mango Season offers insight into the cultural and emotional complexity of diaspora, especially for women. This research comes to the conclusion that diasporic identity is flexible, negotiated, and influenced by both exclusion and belonging.
Reupload file repository 25 Februari 2026_Yudi
Keywords: Diasporic Character’s Struggle; Homeland; he Mango Season